Hubungan Kepercayaan Diri Dengan Gangguan Makan Anorexia Nervosa Pada Remaja Di SMAN 4 Kota Langsa - Sri Ayu Melani; Hasanuddin Hasanuddin; Nina Siti Salmaniah Siregar (Universitas Medan Area, 2021)
One of the effects of the transition period that occurs on young women is the perception that they look beautiful by doing an excessive diet so that it can cause eating disorders that affect themselves and their social relationships. This study aims to see the relationship between self-confidence and eating disorder anorexia nervosa in adolescents. This study uses correlational quantitative methods by analyzing the dynamics between phenomena, both risk factors and effect factors. The design was cross sectional to see the relationship between exposure status (risk factors) and observed effects. The results of the analysis showed that self-confidence had a significant relationship with eating disorder anorexia nervosa in adolescents, amounting to 28.42%. This is indicated by the coefficient value (rx1y = -0.865) with a significance level (p = 0.000 0.01), which is very significant. This means that the hypothesis is accepted, and because rx1y is negative, eating disorder Anorexia Nervosa has a very significant negative relationship with self-confidence.